(untitled) (Bangladesh Journal of Zoology, 2015)
The total fat and fatty acid composition of three commonly consumed small indigenous fish species of Bangladesh, Mola, Amblypharyngodon mola, Jat puti, Puntius sophore and Shar puti, Systomus sarana. Twenty-one types of fatty acids were identified from the extracted oil of these fishes. C16:0 and C18:0 were the predominant saturated fatty acids (SFA), C16:1 ?7 and C18:1 ?9 the main monounsaturated fatty acids (MUFA), while C22:6:4 ?3 (DHA), C20:5 ?3 (EPA) were the main PUFAs. The total ?3 was between 4.28% to17.86% and the total ?6 was between 4.08% to 23.12%. The ?3/ ?6 ratio was between to 0.35% to 1.50%. It is evident from this study that A. mola, P. sophore and S. Sarana are good source of ?3 and ?6 PUFA and their regular consumption will contribute to better health. Bangladesh J. Zool. 43(1): 85-93, 2015